Rejuvenation of Bisaya cultural identity in the landscape development of Taman Tasik and Tamu, Beaufort Sabah - Noorliana Erdenaa Musnin; Musnin Misdih (Akademi Seni dan Teknologi Kreatif, UMS, 2021)
Assimilation in culture and the development of globalization and technology due to the advancement of life can disrupt the peace and harmony of culture. The main focus of the study is to identify Bisaya cultural values and beliefs related to the landscape, identify cultural adaptations and past activities to be interpreted into modern life and to study the relationship between concepts, movements, music and dance rhythms along with belief systems, socioeconomic activities and traditional values of Bisaya culture. The results of the study can also explain the use of dance movements in the master plan design and details of the studied area. The traditional dance movement has its own value and uniqueness where it is also closely related to the life of the Bisaya community. There are several elements of this culture that are used in designing based on the cultural features and styles that applied into landscape design architecture. The implications of the study show that the design in aspect of architectural in the past is not known, when this study is done, the effect is that many people regardless of the Bisaya can recognize the latest designs produced according to the passage of time.